Fenomena K-POP Sebagai Strategi Ekspansi Produk Scarlett - Sabina, Nafiza Kayla; Alvionita; Nursyifa, Putri; Saleh, Mohamad Zein (Business and Investment Review, 2023)
This article examines how implementing an expansion strategy can support the marketing plans of the local Scarlett brand. By conducting an initial study of trends that can influence the scale of sales and this can be used as an expansion strategy carried out using world artists as brand ambassadors. An expansion strategy that focuses on the process by which a company seeks opportunities to expand its business operations beyond the boundaries of existing regions, markets, or businesses. The goal of business expansion is to achieve sustainable growth, increase market share, increase revenue, and create value for shareholders. In this way, using brand ambassadors from Korean artists is the right thing to achieve this expansion strategy. Apart from that, Brand Awareness is also important so that Scarlett becomes a mainstay for consumers. The use of qualitative data with the use of previously collected data certainly supports this article into systematic information that shows evidence that the influence of the Korean Wave in Indonesia is very supportive in terms of economic activity in the business world.